Corona, Forced Migration and Human Rights – Review of a Virtual Lecture Series - Wiese, Lorenz; Bendel, Petra; Fackler, Magdalena (Refugee review, 2022)
This paper sums up the discussions held during a series of online lectures on “Corona, Forced Migration and Human Rights” organised in 2020 by the Centre for Human Rights (CHREN) of Friedrich-Alexander-University Erlangen-Nürnberg (FAU) in Germany within the project FFVT, “Forced Migration and Refugee Studies: Networking and Knowledge Transfer”. The lecture series brought together scientists, journalists, and practitioners in an attempt to analyse the COVID-19 situation for refugees and to identify gaps for future research, policy, and activism. Central to each of these was the human rights classification of the reports as showing that certain human rights are particularly affected by COVID- 19. In three online events, experts examined the pandemic´s impacts on refugees and migrants on different political levels: global, European and national/local. The first one focused on Western Africa and Libya, followed by the situation at the EU external borders, more precisely on the Greek island Lesbos. Finally, the national, regional, and local levels were analysed, scrutinizing the accommodation of refugees in Germany and particularly Bavaria, under COVID-19 conditions. This review combines ad-hoc reports of various practitioners working in the field in different regions and may serve as a basis for more indepth discussions.<br
Keywords: Coronavirus; Lockdown; Refugees; Forced migrants; Immobility; Border closures; Camps; Human rights